Technical report: numerical-analytical algorithm for constructing the envelope of the point mass trajectories in midair / Umi Yasmin Norhani - Norhani, Umi Yasmin (2018)
A projectile is the movement of any object over the air that worked on just by the gravity and air resistance. The motions of a projectile unfaltering by the items starting speed push edge and gravity. When any object is going through the fluid such as water or air, it will experience a backward force which is called as a 'drag force' .This project focuses on the motion of a projectiles with the air drag force is taken into account assumed to be constant proposed by Chudinov (2009).This project also includes constructing of the envelope of a family of trajectories and projectories. The aim of this research is to construct the envelope equation and by using the envelope equation, we can form a formula that can be used for the determination the maximum range of flight. A numerical integration is used to compare these approximate value with analytical values. Also, MATLAB Software are used in solving the numerical integration of the differential system and maple software to generate a graph for the solution.